2011
DOI: 10.1007/s10585-011-9385-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of DDR1 in the gelatinases secretion induced by native type IV collagen in MDA-MB-231 breast cancer cells

Abstract: Discoidin domain receptors (DDRs) are receptor tyrosine kinases that get activated by collagens in its native triple-helical form. In mammalian cells, DDR family consists of two members, namely DDR1 and DDR2, which mediates migration and proliferation of several cell types. DDR1 is activated by native type IV collagen and overexpressed in human breast cancer. Type IV collagen is the main component of basement membrane (BM), and the ability to degrade and penetrate BM is related with an increased potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 103 publications
1
47
0
Order By: Relevance
“…Moreover, MMP-9 is expressed in adult brain neurons and is responsive to changes in neuronal activity (Dzwonek et al, 2004). Combined with the results of previous research (Castro-Sanchez et al, 2011), we hypothesized that MMP-9 overexpression and activation after cerebral ischemic injury may be regulated by its upstream molecule (DDR1) via inflammatory responses, which provided a reliable basis for our next experiments. Our western blotting results showed that phospho-DDR1 levels continued to increase after I/R injury, and the overall activation trend between phospho-DDR1 and MMP-9 was the same.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, MMP-9 is expressed in adult brain neurons and is responsive to changes in neuronal activity (Dzwonek et al, 2004). Combined with the results of previous research (Castro-Sanchez et al, 2011), we hypothesized that MMP-9 overexpression and activation after cerebral ischemic injury may be regulated by its upstream molecule (DDR1) via inflammatory responses, which provided a reliable basis for our next experiments. Our western blotting results showed that phospho-DDR1 levels continued to increase after I/R injury, and the overall activation trend between phospho-DDR1 and MMP-9 was the same.…”
Section: Discussionmentioning
confidence: 72%
“…Since DDR1 plays a role in stabilizing cell-cell junctions through E-cadherin, it may play a valuable role in regulating collective cell migration possibly in cancer metastasis [13]. Prolonged activation of DDR1 is known to upregulate MMPs [1], [5], [14] and MMPs are associated with the invasive and metastatic potential of tumor cells by their ability to degrade extracellular matrix (ECM) [15]. Collagen-induced DDR1 activation can also promote cell survival via anti-apoptotic activity [14].…”
Section: Introductionmentioning
confidence: 99%
“…A study has demonstrated that DDR1 can mediate cell migration by means of regulating the migration suppressor Syk kinase (55), providing further evidence for a pro-migratory role of DDR1. Castro-Sanchez et al (56) demonstrated that in MDA-MB-231 Table I. Expression levels of DDR1 in different types of breast carcinoma.…”
Section: Complex Role Of Ddr1 In Migrationmentioning
confidence: 99%
“…The pro-invasive function of DDR1 may be mediated by the upregulation of the expression of MMPs, particularly MMP-2 and MMP-9. The elevated expression of MMPs contributes to the degradation of extracellular matrix components, facilitating cancer cell invasion (56). Products that can suppress the pro-invasion function of DDR1 have been developed; Santa Cruz (54) Hs578T ( Biotechnology have developed two novel antibodies that can inhibit DDR1a-mediated Matrigel invasion (68) and DDR1 activation in human MDA-MB-231 cells (58).…”
Section: Ddr1 In Breast Carcinoma Invasionmentioning
confidence: 99%